2017
DOI: 10.1155/2017/3674045
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Bone Turnover Markers in Long Bone Nonunions Treated with a Regenerative Approach

Abstract: In this clinical trial, we investigated if biochemical bone turnover markers (BTM) changed according to the progression of bone healing induced by autologous expanded MSC combined with a biphasic calcium phosphate in patients with delayed union or nonunion of long bone fractures. Bone formation markers, bone resorption markers, and osteoclast regulatory proteins were measured by enzymatic immunoassay before surgery and after 6, 12, and 24 weeks. A satisfactory bone healing was obtained in 23 out of 24 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Levels reached baseline by 24 weeks. Further a remarkable decrease in BAP was observed at all time points in a single patient who experienced atreatment failure (Granchi et al, 2017).…”
Section: Discussion:-mentioning
confidence: 77%
See 1 more Smart Citation
“…Levels reached baseline by 24 weeks. Further a remarkable decrease in BAP was observed at all time points in a single patient who experienced atreatment failure (Granchi et al, 2017).…”
Section: Discussion:-mentioning
confidence: 77%
“…BAP is found in the plasma membrane of osteoblasts (Gothlin and Ericsson, 1973). A crossreactivity of approximately 15% between liver and bone ALP can affect measurements in individuals with high liver ALP (Granchi et al, 2017). Patients with liver disease or deranged liver function tests were excluded from the study.…”
Section: Discussion:-mentioning
confidence: 99%
“…Interestingly, it was observed that MSX2, which has been shown to suppress ALP transcription at the promoter level and to antagonize osteoblast differentiation 32,33 , was up-regulated in CBMSCs compared www.nature.com/scientificreports/ www.nature.com/scientificreports/ to BMSCs. Since ALP has been shown to be a marker of bone healing in patients 7 , this may represent an important difference between the two MSC sources in terms of their osteogenesis. Intriguingly, CBMSC ALP gene expression was rescued by chondrogenic priming and in vitro culture on BCP biomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is particularly suited to complex skeletal injuries lacking sufficient osteogenic potential. Although significant progress has been made in this field in recent years and several clinical studies are under way both in Europe and the United States, 76 a better understanding of the role of each of the components and the interactions amongst them remains to be reached. In particular, the development of scaffolds that are able not only to support cell attachment and growth, but to also provide the adequate temporary niche to the cells and instruct them in the right direction, may represent a significant step forward for the efficacy of this therapeutic approach.…”
Section: Open Challenges In the Design Of High Performance Synthetic mentioning
confidence: 99%